Occupational Stress and General Well-being among Police (Journal of Energy and Safety Technology (JEST), 2022)
Stress at the workplace is a global issue faced by individuals and organisations. Police officers are considered to be one of the most stressful occupations globally. This study aimed to determine factors that cause occupational stress and general well-being, the relationship between operational stress and general well-being, organisational stress and general well-being, and compare the level of occupational stress between departments. This cross-sectional study utilised the stratified random sampling procedure and recruited 107 police from a Districts Police Headquarters in Kedah. The Police Stress Questionnaire (PSQ) and General Health Questionnaire (GHQ-12) was used. The data has been entered and analysed using (SPSS) version 24. Perceived operational and organisational stress prevalence among the study population was moderate, with 50% operational stress (moderate stress in 39.3% and high stress in 10.3%), while organisational stress reported 60% (moderate stress in 36.4% and increased stress in 23.4%). The most common stressors reported for operational stress were negative comments from the public (19.6%), while organisational stress was staff shortage (30.8%). There is a significant negative correlation between operational and organisational stress and general well-being with r = -0.806 and r = -0.786. This study strengthens the findings that police job was stressful. The action needs to be taken by the organisational so that occupational stress can be reduced and increase the well-being of the police officers.
Keywords: occupational stress; general well-being; operational stress; organisational stress; police